(untitled) (Research, Society and Development, 2025)
The skin is the largest organ of the human body and plays a fundamental role in protecting against external aggressions and maintaining homeostasis. With aging, cellular changes and alterations in the extracellular matrix occur, leading to a loss of elasticity, hydration, and increased susceptibility to damage. Scientific evidence suggests that the intestinal microbiota influences skin health through the gut-skin axis, modulating inflammatory and immune processes that impact skin aging. This study aims to investigate the relationship between the intestinal microbiota and skin aging, analyzing how its balance or dysbiosis can affect skin health. It is a narrative literature review conducted according to PRISMA guidelines. Databases such as PubMed, SciELO, and the Virtual Health Library (VHL) were consulted using descriptors in Portuguese and English, such as "microbiota," "skin aging," and "skin."The results indicate that the composition of the intestinal microbiota can modulate the inflammatory and oxidative response of the skin, directly influencing its aging process. Studies suggest that probiotic supplementation, such as Lactobacillus plantarum HY7714, can improve hydration, elasticity, and reduce facial wrinkles. It is concluded that maintaining a balanced gut microbiome may positively contribute to skin health, delaying the signs of skin aging. Thus, strategies aimed at balancing the intestinal microbiota may represent a promising approach in preventive dermatology.